Prêtres en Gaule mérovingienne. By Robert Godding. Pp. lxx + 559. Map. (Subsidia Hagiographica, 82.) Brussels: Société des Bollandistes, 2001. isbn 2 87365 010 9. Paper €110 - Stancliffe, Clare (The journal of theological studies, 2005)
There have been several studies of bishops in Merovingian Gaul, but none, hitherto, of priests. The reason is not far to seek: bishops were key figures in society as in church, and so figure prominently in the sources. For priests, however, the sources are patchy: we have prescriptive canons from synods, and individual references and stories in the works of Gregory of Tours and of Venantius Fortunatus, and in the considerable body of Merovingian saints’ Lives. As a Bollandist, Godding is well versed in the latter; and one excellent feature of this book—and one which will render it valuable to all scholars of Merovingian Gaul—is his annotated list of almost one hundred Lives of Gallic saints.